ATRV-mini platform development for navigation and mapping - Talens, Angelito N. (2007)
In this project, we developed sensor modules and motor controller for the ATRV-mini intended for outdoor navigation and mapping. The modules will be integrated through an on-board FPGA Development Board. These sensors provided pitch and roll angles, heading for direction, relative displacement, relative proximity of objects, and as well as diagnostic sensors for temperature and power supply monitoring. Gathered data was transmitted through an RF link and received by a computer then displayed on a Graphical User Interface program.